Does a growth mindset reduce procrastination and perfectionism? - Bown, Erica (My University, 2023)
Research has consistently found a positive relationship between fear of failure (FoF) and both perfectionism and procrastination, which are both positively correlated with stress. Many university students report high levels of perfectionism, procrastination, and stress; thus, interventions to help reduce these characteristics are needed. Individuals who have a growth mindset (GM) are more likely to view challenges and failures as opportunities to learn and grow rather than as obstacles. The present study investigated the effect of a GM intervention on procrastination and negative perfectionism. We hypothesized that students who received the GM intervention would report lower procrastination due to FoF and lower negative perfectionism than students who did not receive the GM intervention. In Part 1, all participants completed questionnaires assessing personality, stress, perfectionism, procrastination, and GM. Participants in the GM intervention group were shown a video and infographic about GM and its benefits and were sent reminder emails about the benefits of GM once a week for four weeks. After four weeks, participants completed all measures again. Our results show that the GM intervention failed to produce any significant changes in GM, negative perfectionism, and procrastination due to FoF. We further show positive relationships between stress and both procrastination due to FoF and negative perfectionism. Future research will investigate a more effective GM intervention. Our results confirm that university students’ stress is highly associated with negative perfectionism and procrastination due to FoF and that students may benefit from stress reduction methods that specifically target perfectionism and FoF.
Presented on April 20, 2023 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: fear of failure; growth mindset; perfectionism; procrastination; stress